The phonological and morphological integration of English borrowings in modern Japanese - Shyi Nian Ong (Journal of Modern Languages)
The study discusses how the modernization of the Japanese lexicon has been helped, and in some cases, hindered, by the influence of foreign loanwords or gairaigo. The subject of gairaigo's influence on Japanese has not been investigated in a systematic manner and according to modern linguistic principles and procedures. As such this study hopes to contribute in some measure to an understanding of the nature of that contact. The main purpose of this study is to examine the linguistic processes, namely phonological and morphological processes, by which English has influenced the lexical expansions of the Japanese language and to investigate the integration of borrowed innovations and their impact on the structure of Japanese.